Early-blind human subjects localize sound sources better than sighted subjects - Lessard, N.; Paré, M.; Lepore, F.; Lassonde, M. (Nature (London), 1998)
Do blind persons develop capacities of their remaining senses that exceed those of sighted individuals? Besides anecdotal suggestions, two views based on experimental studies have been advanced 1 . The first proposes that blind individuals should be severely impaired, given that vision is essential to develop spatial concepts 2 . The second suggests that compensation occurs through the remaining senses, allowing them to develop an accurate concept of space 3 . Here we investigate how an ecologically critical function, namely three-dimensional spatial mapping, is carried out by early-blind individuals with or without residual vision. Subjects were tested under monaural and binaural listening conditions. We find that early-blind subjects can map the auditory environment with equal or better accuracy than sighted subjects. Furthermore, unlike sighted subjects, they can correctly localize sounds monaurally. Surprisingly, blind individuals with residual peripheral vision localized sounds less precisely than sighted or totally blind subjects, confirming that compensation varies according to the aetiology and extent of blindness 4 . Our results resolve a long-standing controversy in that they provide behavioural evidence that totally blind individuals have better auditory ability than sighted subjects, enabling them to compensate for their loss of vision.